Revised Draft Second Five Year Plan Assam as Provisionally Approved by the Planning Commission Part II (Details of Development Envisaged in Different Sectors) - Planning Commission (Planning Commission, 1956)
During the War, the Government of India launched the Grow-More-Food Drive in 1942-43 to step up the production of all agricultural commodities. But at the end of the War, in view of the limited resources of the country and on account of the acute scarcity of food, the Government ol India decided to concentrate on the production of food-grains only. So when the First Five Year Plan of the State was drawn up, it was decided to concentrate on schemes which had the limited objective of increasing food production only, as they were also the schemes which were eligible for Grow-More-Food assistance.
Department of Planning and Development, Government of Assam